Team managers' knowledge of the role of physiotherapy in South African Soccer Teams in the Premier Soccer League - Motha, Sergant Given (University of Limpopo (Medunsa Campus), 2009)
Background information of the study: Physiotherapists play an important role in soccer teams. This role includes prevention of injury, treatment, education, and exercises. There is a dearth of information in some areas on the part of sports managers on the role of the physiotherapist in a team. Purpose: The purpose of this study was to establish the knowledge of South African team managers on the role of the physiotherapist in the Premier Soccer League (PSL) teams. Objectives: The objectives of this study were to establish team managers’ knowledge of the role of physiotherapists in the prevention and treatment of soccer injuries and evaluate their knowledge of the injuries managed by physiotherapists. Setting: PSL teams in South Africa Design: A descriptive survey design with a close-ended questionnaire was used in this study. Methodology: A quantitative research approach was employed in this study. Descriptive statistics were used to analyze the data set and a rating scale was used to determine the knowledge of team managers. Results: Out of the 16 teams in the PLS, 13 team managers participated in the study and their average knowledge was 79%. Five (38%) had administrative qualifications while eight (62%) did not include their qualifications. All 13 respondents indicated that warm up, cool down and stretching reduces the risk of injuries. Eleven (77%) reported that prophylactic strapping reduces risk of injuries. All participants agreed that physiotherapeutic treatment includes massage, electric machines and ice. They also mentioned that exercises can be done by the physiotherapist, though only three (23%) believed that the physiotherapist could conduct physical training. Conclusion: This study revealed that team managers have good knowledge of the role of the physiotherapist in soccer, with regard to prevention and treatment of injuries in sport.
Thesis (MSc (Physiotherapy))--University of Limpopo (Medunsa Campus), 2009.
Keywords: Managers' knowledge; Physiotherapy; Premier Soccer League